Android-Based Tutorial Mobile Development Equipped with Corrective and Constructive Feedback Materials for Data Transmission and Storage - Fatmawati Ramadani; Sulur Sulur; Nugroho Adi Pramono; Budi Nurani; Catur Wigiyati (Jurnal Riset Pendidikan Fisika, 2022)
This study aims to develop a mobile tutorial application on data transmission and storage material as a learning medium for high school students. The study employed a research and development approach with a 4D model (Define, Design, Develop, and Disseminate). However, the study was partly carried out using the Develop stage. Based on the results of research and development, the results of the validation of the entire product were obtained with an average score of 3.70 with valid criteria (without revision) and the results of the readability test were 94% with legibility criteria. This shows that the Android-based mobile tutorial equipped with corrective and constructive feedback on data transmission and storage materials for high school students can be used by teachers and students for independent learning.Keywords:   mobile tutorial,  Android, corrective feedback, constructive feedback, data transmission and storageABSTRAKPenelitian ini bertujuan untuk menghasilkan aplikasi mobile tutorial pada materi transmisi dan penyimpanan data sebagai media pembelajaran siswa SMA/MA. Penelitian ini merupakan penelitian dan pengembangan dengan model 4D (Define, Design, Develop, dan Disseminate) namun hanya dilakukan hingga tapah Develop. Berdasarkan hasil penelitian dan pengembangan, diperoleh hasil validasi keseluruhan produk dengan skor rata-rata sebesar 3,70 dengan kriteria valid (tanpa revisi) dan diperoleh hasil uji keterbacaan 94% dengan kriteria terbaca. Hal ini menunjukkan bahwa mobile tutorial berbasis android dilengkapi corrective dan constructive feedback pada materi transmisi dan penyimpanan data untuk siswa SMA/MA dapat digunakan oleh guru maupun siswa sebagai media pembelajaran untuk belajar mandiri.